Answer:
as
so
the statement B i.e. [tex]a\:-\:\left(b\:+\:c\right)\:=\:\left(a\:-\:b\right)\:+\:c[/tex] can not be justified by one
of the properties of real numbers.
Step-by-step explanation:
The statement B cannot be justified by one of the properties of real numbers,
Given the statement
[tex]a\:-\:\left(b\:+\:c\right)\:=\:\left(a\:-\:b\right)\:+\:c[/tex]
solving the L.H.S of the above equation
[tex]a\:-\:\left(b\:+\:c\right)[/tex]
Distribute Parenthesis
[tex]=a\:-\left(b\right)-\left(c\right)[/tex]
[tex]\mathrm{Apply\:minus-plus\:rules}[/tex]
[tex]+\left(-b\right)=-b, +\left(-c\right)=-c[/tex]
[tex]=a-b-c[/tex]
so
[tex]a-\left(b+c\right)=a-b-c[/tex]
Therefore, [tex]a\:-\:\left(b\:+\:c\right)\:=\:\left(a\:-\:b\right)\:+\:c[/tex] can not be justified by one
of the properties of real numbers.